1993
DOI: 10.1128/aac.37.12.2733
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibilities of Gardnerella vaginalis

Abstract: The in vitro susceptibilities of 93 clinical isolates of Gardnerella vaginalis to 25 antimicrobial agents were determined by the agar dilution method. All isolates were susceptible to penicillin, ampicillin, erythromycin, clindamycin, chloramphenicol, and trimethoprim. Activity was poor for vancomycin, LY146032, the cephalosporins, ciprofloxacin, and imipenem. Some resistance was observed with tetracycline and minocycline. The MICs of metronidazole paralleled those of tinidazole, with the hydroxymetabolite of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 19 publications
(12 reference statements)
3
17
1
Order By: Relevance
“…Metronidazole was partially active against G. vaginalis (MICs, Ͻ0.125 to 256 g/ml) and A. vaginae (MICs, 8 to 256 g/ml). These results are also in accordance with previously published data (5,12,15). Nifuratel was more active on G. vaginalis and A. vaginae than metronidazole, with MICs ranging from Ͻ0.125 to 4 g/ml and from Ͻ0.125 to 1 g/ml, respectively.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…Metronidazole was partially active against G. vaginalis (MICs, Ͻ0.125 to 256 g/ml) and A. vaginae (MICs, 8 to 256 g/ml). These results are also in accordance with previously published data (5,12,15). Nifuratel was more active on G. vaginalis and A. vaginae than metronidazole, with MICs ranging from Ͻ0.125 to 4 g/ml and from Ͻ0.125 to 1 g/ml, respectively.…”
supporting
confidence: 82%
“…Our results (Table 1) show that clindamycin is highly active against both G. vaginalis (MIC for 90% of the strains tested [MIC 90 ], 0.25 g/ml) and A. vaginae (MIC 90 , Ͻ0.125 g/ml), in accordance with previous studies on G. vaginalis (12,15) and A. vaginae (5). Metronidazole was partially active against G. vaginalis (MICs, Ͻ0.125 to 256 g/ml) and A. vaginae (MICs, 8 to 256 g/ml).…”
supporting
confidence: 80%
“…This is probably due to the inactivation of ampicillin by beta-lactamases produced by other vaginal anaerobes and not specifically by G. vaginalis [25,26]. A high rate of ampicillin resistance and intermediate resistance was observed.…”
Section: Discussionmentioning
confidence: 88%
“…Clindamycin has activity against these organisms, while metronidazole generally does not. A possible explanation for metronidazole having activity against these organisms is that previous studies have reported the hydroxymetabolite of metronidazole, a compound formed when metronidazole is metabolized by the liver or from the breakdown of metronidazole by anaerobic bacteria during its action, has antimicrobial activity and may have activity against G. vaginalis (13,14,26,28). A previous study has suggested that eradication of nitroimidazole-susceptible anaerobic organisms may lead to a decreased colonization by nonsusceptible organisms like G. vaginalis and M. hominis (9).…”
Section: Discussionmentioning
confidence: 99%